NMDA receptor-dependent presynaptic inhibition at the calyx of Held synapse of rat pups - Oshima-Takago, Tomoko (Open Biol, 2017)
N-Methyl-d-aspartate receptors (NMDARs) play diverse roles in synaptic transmission, synaptic plasticity, neuronal development and neurological diseases. In addition to their postsynaptic expression, NMDARs are also expressed in presynaptic terminals at some central synapses, and their activation modulates transmitter release. However, the regulatory mechanisms of NMDAR-dependent synaptic transmission remain largely unknown. In the present study, we demonstrated that activation of NMDARs in a nerve terminal at a central glutamatergic synapse inhibits presynaptic Ca(2+) currents (I(Ca)) in a GluN2C/2D subunit-dependent manner, thereby decreasing nerve-evoked excitatory postsynaptic currents. Neither presynaptically loaded fast Ca(2+) chelator BAPTA nor non-hydrolysable GTP analogue GTPγS affected NMDAR-mediated I(Ca) inhibition. In the presence of a glutamate uptake blocker, the decline in I(Ca) amplitude evoked by repetitive depolarizing pulses at 20 Hz was attenuated by an NMDAR competitive antagonist, suggesting that endogenous glutamate has a potential to activate presynaptic NMDARs. Moreover, NMDA-induced inward currents at a negative holding potential (−80 mV) were abolished by intra-terminal loading of the NMDAR open channel blocker MK-801, indicating functional expression of presynaptic NMDARs. We conclude that presynaptic NMDARs can attenuate glutamate release by inhibiting voltage-gated Ca(2+) channels at a relay synapse in the immature rat auditory brainstem.